PENGUATAN UMKM PENJUALAN PRODUK KERIPIK SELADA DI DESA SUKO MULYO - Juwari, Juwari; Mayana Asid, Gatik; Taufik Rohman, Dwi; Hadiyatno, Didik; Anam, Hairul (Fakultas Ekonomi Universitas Balikpapan, 2023)
Real Work Lecture is a community service by going directly to the field carried out by lecturers and students. In carrying out service to Suko Mulyo Village, a strengthening of Micro, Small and Medium Enterprises (MSMEs) Sales of Lettuce Chips Products was carried out. The purpose of this service is to provide understanding and knowledge to Mrs. PKK's partners about selling lettuce raw materials into lettuce chips. This devotion is carried out by selling lettuce chip products.